Pemanfaatan Instrumen Tes dan Nontes Pada Layanan Konseling - M. Fahli Zatrahadi; Daharnis Daharnis; A. Muri Yusuf (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Utilization of test and non-test instruments in counseling services at SMKN 1 Base Lesung. This research finds out the benefits of test and non-test instruments given to students in counseling services. Research method uses qualitative research with the following stages: Determine questions, collect informant data, get data, and report. The informants comprised three supervisors at the SMKN 1 Pangkalan Lesung school. Data analysis using Nvivo coding process. The results of the study show that implementing the provision of test or non-test instruments is related to each other in order to get more effective assessment results. Even though in its implementation it encountered problems such as time problems, services, data processing and presentation of results, school counselors still carried the provision of both test and non-test instruments out. Both test and non-test instruments are used according to the specific program and its functions. This happens because the conditions in the field are different.